Understanding evolution in Poales: Insights from Eriocaulaceae plastome - Darshetkar, Ashwini M. (PLoS One, 2019)
In this study, we report the plastome of Eriocaulon decemflorum (Eriocaulaceae) and make an effort to understand the genome evolution, structural rearrangements and gene content of the order Poales by comparing it with other available plastomes. The size of complete E. decemflorum plastome is 151,671 bp with an LSC (81,477bp), SSC (17,180bp) and a pair of IRs (26,507 bp). The plastome exhibits GC content of 35.8% and 134 protein-coding genes with 19 genes duplicated in the IR region. The Eriocaulaceae plastome is characterized by the presence of accD, ycf1 and ycf2 genes and presence of introns in clpP and rpoC1 genes which have been lost in the Graminid plastomes. Phylogenomic analysis based on 81 protein-coding genes placed Eriocaulaceae sister to Mayacaceae. The present study enhances our understanding of the evolution of Poales by analyzing the plastome data from the order.